DEVELOPING SOCIAL SKILLS FOR CHILDREN AND YOUTH WITH DISABILITIES DEPRIVED OF PARENTAL CARE IN BULGARIA - Popova, Desislava Angelova (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Current study examines the impact of systematic group work based on non verbal communication techniques on youth with special needs with severe communication disorders who are grown up outside their families and in residential homes in Bulgaria. Scientific experiment detects certain indicators in intervention and nonintervention groups by conducting structured interviews as well as objective monitoring and filling in checklists. The tracked indicators are: a way youth are expressing their needs; initiative and persistence of youth in activities; way of communication, and aggressive manifestations. Children and youth deprived of parental care living across Bulgarian residential homes participated in experimental alternative communication group work for 6 months by a team of specialists and volunteers and under the supervision of a psychotherapist. Another youth from same age risk group remained non intervention. A total of 24 group work sessions have been completed. Specialists working with both groups completed check lists and repeated measures assessed changes in the behavior of some participants towards increased engagement in activities, retaining attention over a longer period of time, development of social skills such as line waiting, privacy, remote contact initiation, expressing desires by means of higher levels of ontogenetic development. A functional assessment is applied tailored to the individual features and capabilities of each participant regardless of age taking into account their development. In connection with the observed effects of the applied impact, there is a need for persistence in the implementation of the classes and incorporation of similar principles in the everyday life of the users of this type of residential homes in the Republic of Bulgaria.